Prevalence and Correlates of HIV Infection among Female Sex Workers in Two Mexico-U.S. Border Cities - Patterson, Thomas L. (2008)
BACKGROUND: We examined HIV prevalence and correlates among female sex workers (FSWs) in Tijuana and Ciudad Juarez, two large Mexico-U.S. border cities. METHODS: FSWs aged ≥18 years underwent interviews and testing for HIV, syphilis, gonorrhea and Chlamydia. Logistic regression identified factors associated with HIV infection. RESULTS: Of 924 FSWs, prevalence of HIV, gonorrhea, Chlamydia and syphilis titers >1:8 was 6%, 6.4%, 13% and 14.2%. Factors independently associated with HIV were injecting cocaine (OR= 2.96), smoking/snorting/inhaling methamphetamine (OR=3.32) and having syphilis titers >1:8 (OR= 4.16). CONCLUSIONS: Culturally appropriate interventions are needed to identify and treat ulcerative STIs and reduce HIV risks associated with stimulants among FSWs in the Mexico-U.S. border region.